PREDICTIVE POLICING BY BHABINKAMTIBMAS AS A SOLUTION TO ADDRESS CRIMINALITY IN CILEMPUNG VILLAGE, PASIRJAYA, KARAWANG - Sucita, Novia; Nita, Surya; Muriman, Chairul (Ridwan Institute, 2024)
The Karawang Regency faces a significant increase in the number of crimes, being a major concern due to its disruptive impact on the community as well as serious challenges for law enforcement and local governments. In order to respond to the various problems faced by Bhabinkamtibmas in the field, support and strengthening are needed with the right policing program. The research contributes to the field of public security by introducing a Predictive Policing framework tailored to the needs of Cilempung Village, Karawang, utilizing information technology and data analysis to identify crime patterns and predict potential crimes. The study provides insights into the factors influencing crime rates and offers practical strategies for implementing predictive polcing in local communities, ultimately aiming to enhance public safety and maintain social order.